Strategi Guru Dalam Menanamkan Sikap Toleransi Melalui Pendidikan Multikultural - Hidayatullah, Risky; Ubabuddin, Ubabuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Multicultural education serves as a crucial instrument in shaping students' tolerance in a heterogeneous school environment. The role of teachers in implementing multicultural education is essential, as they act as learning facilitators who instill the values of tolerance, democracy, and humanism. This study aims to analyze teachers' strategies in fostering tolerance through multicultural education. Using a literature review method, this research examines various strategies implemented in primary and secondary schools to cultivate students' tolerance. The findings indicate that the main strategies employed by teachers include interactive learning models, the use of multicultural-based media, inclusive classroom management, and collaboration with parents and the community.